Empowering Communities Through Knowledge: Healthcare Workers' Role in Infection Prevention - Alaqidi , Asma sayer; Alnami, Alaa Abdullah; Alqurashi , Najla Dakhilallah; Alharbi , Salwa Abdullah; Alwaal, Nouf Tawfiq; Alanazi , Ohud Saud; Khwaji, Ahmed Hadi; Khwaji , Turkey Hadi; Alkhodeir, Sahaab Fathi; Alwaal , Latifa Tawfiq (Journal of Ecohumanism, 2025)
Healthcare workers play a critical role in empowering communities through education on infection prevention. This article examines their influence as educators, exploring strategies used to disseminate knowledge, overcome barriers, and foster sustainable health practices. Drawing from case studies and evidence-based research, the analysis highlights how effective communication and community engagement by healthcare workers lead to improved infection control and reduced disease transmission. The findings emphasize the need for capacity building, cultural sensitivity, and technology integration to enhance the reach and impact of educational initiatives. This study underscores the transformative potential of healthcare workers in creating healthier, well-informed communities.